The Top 5 e-commerce Competitive Advantages in Hungary - Tamás, Szikszai (International Journal of Engineering and Management Sciences, 2022)
Abstract. In my article, I map out the key competitive advantages that are essential to online commerce, online store sales, success, and popularity. There is a wealth of literature on the subject. Year after year, more and more research and surveys are conducted on customer value, shopping habits, consumer behavior, digital transformation, which I would like to summarize and articulate, and highlight the main elements without which online sales would not be effective.